THE INFLUENCE OF TELEVISION SERIALS ON FORMING NATIONAL VALUES OF YOUNG PEOPLE - Димніч, Н. Д. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
In the article the task of modern television is considered in the context of becoming of national costs of personality, the psychological aspects of process of national self-definition and place are found out in him modern televisional serials.